Tetrahydropyranyl: A Non‐aromatic, Mild‐Acid‐Labile Group for Hydroxyl Protection in Solid‐Phase Peptide Synthesis. Issue 2 (8th March 2017) - Sharma, Anamika; Ramos‐Tomillero, Iván; El‐Faham, Ayman; Rodríguez, Hortensia; de la Torre, Beatriz G.; Albericio, Fernando
Abstract: The use of the tetrahydropyranyl (Thp) group for the protection of serine and threonine side‐chain hydroxyl groups in solid‐phase peptide synthesis has not been widely investigated. Ser/Thr side‐chain hydroxyl protection with this acid‐labile and non‐aromatic moiety is presented here. Although Thp reacts with free carboxylic acids, it can be concluded that to introduce Thp ethers at the hydroxyl groups of N‐protected Ser and Thr, protection of the C‐terminal carboxyl group is unnecessary due to the lability of Thp esters. Thp‐protected Ser/Thr‐containing tripeptides are synthesized and the removal of Thp studied in low concentrations of trifluoroacetic acid in the presence of cation scavengers. Given its general stability to most non‐acidic reagents, improved solubility of its conjugates and ease with which it can be removed, Thp emerges as an effective protecting group for the hydroxyl groups of Ser and Thr in solid‐phase peptide synthesis. Abstract : Save the alcohol : The tetrahydropyranyl (Thp) group is characterized by its ease of introduction, stability under basic conditions, versatility and atom economy. It has proved to be an effective non‐aromatic acid‐labile moiety for the protection of the hydroxyl groups of serine and threonine residues in solid‐phase peptide synthesis.